2013
DOI: 10.1016/j.jcin.2013.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome After Crush Versus Culotte Stenting of Coronary Artery Bifurcation Lesions

Abstract: At 36-month follow-up, the clinical outcomes were similar for patients with coronary bifurcation lesions treated with the culotte or the crush stent technique. (Nordic Bifurcation Study. How to Use Drug Eluting Stents [DES] in Bifurcation Lesions? NCT00376571).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 14 publications
1
44
0
Order By: Relevance
“…Multiple studies have been designed to compare different DS strategies. The Nordic II study showed that definite ST was lower in the crush (1.4%) versus the culotte group (4.7%) respectively; however, this did not reach statistical significance ( P = 0.09) . The DKCRUSH‐III study reported a significantly increased definite ST rate (3.4%) in the culotte group versus DK crush group (0%; P = 0.007) .…”
Section: Discussionmentioning
confidence: 98%
“…Multiple studies have been designed to compare different DS strategies. The Nordic II study showed that definite ST was lower in the crush (1.4%) versus the culotte group (4.7%) respectively; however, this did not reach statistical significance ( P = 0.09) . The DKCRUSH‐III study reported a significantly increased definite ST rate (3.4%) in the culotte group versus DK crush group (0%; P = 0.007) .…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, large-scale direct comparisons of BP-BES with the thinner-strut PP-EES have shown similar safety and efficacy at one year 10,18 , and the further increment of definite stent thrombosis from one to five years in the LEADERS trial was limited to 0.7%, suggesting a very low risk of stent thrombosis after the first year 9 . Similarly, the definite stent thrombosis rate three years after treatment of coronary bifurcation lesions with Axxess in combination with first-generation sirolimus-eluting 20 .…”
Section: Discussionmentioning
confidence: 99%
“…The randomized Nordic-Baltic IV 65 trial showed a trend toward improved midterm outcome when using a two-stent technique compared to provisional stenting in bifurcations with large SBs (≥2.75 mm) having >50% diameter stenosis in the SB. A similar signal was supported by the DKCRUSH II trial 16 and by a subgroup analysis of the Tryton IDE study 63 (EuroPCR 2014).…”
Section: After Pci Stent Expansion and Appositionmentioning
confidence: 99%